2022
DOI: 10.3390/ijerph19159582
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Optimization Strategy of an Ecological Network in Mountainous Areas: A Case Study in Southwestern Hubei Province, China

Abstract: High-intensity urban development and economic exploitation have led to the fragmentation and isolation of regional habitat patches, and biodiversity is under serious threat. Scientific identification and effective optimization of ecological networks are essential for maintaining and restoring regional ecosystem connectivity and guiding sustainable socio-economic development. Taking the mountainous areas of southwest Hubei Province (MASHP) in central China as an example, this study first developed a new integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…This highly productive environment supports diverse micro‐habitats and ecological niches for wildlife (Zuo et al. 2022). This region is also rich in economically important mineral deposits resulting from a series of volcanic eruptions, magma intrusions, and tectonic changes during its geological history (Yang et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This highly productive environment supports diverse micro‐habitats and ecological niches for wildlife (Zuo et al. 2022). This region is also rich in economically important mineral deposits resulting from a series of volcanic eruptions, magma intrusions, and tectonic changes during its geological history (Yang et al.…”
Section: Methodsmentioning
confidence: 99%
“…These climatic conditions support climax vegetation of mountain evergreen deciduous broad-leaved mixed forest, influenced by topography and elevation. This highly productive environment supports diverse micro-habitats and ecological niches for wildlife (Zuo et al 2022). This region is also rich in economically important mineral deposits resulting from a series of volcanic eruptions, magma intrusions, and tectonic changes during its geological history (Yang et al 2016).…”
Section: Study Areamentioning
confidence: 99%
“…Fragmentation refers to the process by which a large continuous distribution of natural habitat is separated into many smaller patches by other unsuitable habitats under the influence of human activities and natural disturbances [ 11 , 12 ]. The multiple negative impacts of the fragmentation process, such as the reduction of natural habitat area, the reduction of connectivity between habitat patches, and the continuous decline of habitat quality, will pose serious challenges to human well-being and regional sustainable development [ 13 , 14 , 15 ]. Initially, a density-dependent reproduction and survival simulation model was developed, and it was concluded that the degree of fragmentation of nature reserves was positively correlated with the species extinction probability [ 16 ].…”
Section: Introductionmentioning
confidence: 99%